CHANGE OF THE ROLE OF THE OIL COMPLEX IN STRUCTURE OF WORLD POWER BALANCE IN THE CONDITIONS OF GLOBALIZATION OF INTERNATIONAL ECONOMIC RELATIONS - E. Makhankov (Вестник университета, 2016)
In the article features of formation of global strategy of the largest Russian oil companies are estimated. The role of transactions on merges and acquisitions in realization of these strategy is shown. Examples of the specific projects aimed at the development of strategy are given. The most effective directions of realization of the external economic strategy of the Russian vertically integrated oil companies are offered.